Patients With Immunoglobulin A Nephropathy Show Abnormal Frequencies of B Cell Subsets, Unconventional T Cells, and High Levels of Galactose-Deficient IgA1–Coated Gut Bacteria - Micaela Gentile; Nina Goerlich; I-Ju Lo; N. Eric Olson; Mark McConnell; Johannes Pospiech; Tobias Bohnenpoll; Philipp Skroblin; Olivier Radresa; Uwe Andag; Kirk N. Campbell; Kristin Meliambro; et al. (Kidney International Reports)
Introduction: Mucosal inflammation is involved in the pathophysiology of immunoglobulin-A nephropathy (IgAN); however, peripheral immune phenotype analyses of patients with IgAN often do not include unconventional T cells, the major subset in mucosal immunity. Methods: We measured serum total IgA, galactose-deficient IgA1 (gd-IgA1), secretory IgA (SIgA), B cell-activating factor (BAFF), and A proliferation-inducing ligand (APRIL) in 66 patients with IgAN and 30 healthy controls (HCs). We also quantified the total IgA and gd-IgA1 in stool supernatant along with the same coated on bacteria. In 35 patients and 14 controls, we performed extensive phenotyping using cytometry by Time-of-Flight (CyTOF) of circulating immune cells, including unconventional T cells (mucosal associated invariant T [MAIT] cells, γδ T, and natural killer [NK] T cells). The results were validated using RNAseq data from a larger cohort of 179 patients with IgAN, 140 patients with minimal change disease, and 91 HCs. Results: Patients with IgAN had higher circulating levels of total IgA, gd-IgA1, and APRIL, and higher IgA and gd-IgA1-coated gut bacteria than controls, whereas serum levels of SIgA and BAFF did not differ between groups. Patients with IgAN showed more class-switched memory (CSM) and double negative (DN) B cells than controls. MAIT cells and γδ T cells were significantly lower, and CD4−CD8− NK T cells were significantly higher in patients with IgAN than in HCs. We validated the significant decrease in MAIT cells in an independent cohort of patients with IgAN. Conclusion: The data indicate that patients with IgAN have increased circulating CSM and DN B cells associated with abnormal T cell immunity, involving defects in unconventional T cell frequency. This may suggest putative alterations at mucosal sites because of cell migration leading to altered IgA production.